Challenges of International Students in Filing Taxes and Using Tax Services in Canada - Yan, Lian (Université d'Ottawa / University of Ottawa, 2020)
Starting new lives in an unfamiliar environment, international students may encounter difficulties in dealing with their tax reports. They are often faced with challenges about the ways in which tax works. In this thesis, three main tax filing challenges of international students are defined: identity and tax, tax complexity and tax knowledge. As previous tax literature has not sufficiently explored the tax experiences of international students, there is a need for research that addresses the lived tax experiences of this minority group. Therefore, this thesis aims to explore the phenomenon of international students’ tax filings. Providing an interpretive exploration of international students’ tax-related challenges, the researcher interviewed 20 international students to explore what challenges they are experiencing and how they are experiencing the challenges. To deepen the understanding of tax filing challenges, the researcher uses functional attitude theory (FAT) to analyze international students’ lived experiences and employs a phenomenological approach to gain profound insights into international students’ tax filings. Looking into international students’ functional attitudes towards the tax flings reveals the impacts that the challenges have on their perspectives of tax filings. The findings show that international students make tax decisions in relation to their utilitarian attitudes, willingness of social adjustment, different values and knowledge about tax. Particularly, this thesis contributes to the understanding regarding the international students’ tax filing challenges in Canada.
Keywords: Tax filing challenges; Identity; Tax complexity; Tax knowledge; Functional attitudes